The Street Over the River: Mediation Between Hygiene and Urbanism Through Drawing in the City of Porto - Marques da Silva, Mariana (Vysoké učení technické v Brně,Fakulta architektury, 2019)
Urban transformations were developed in the city of Porto during the second half of the 19th century, particularly between 1870-1890, when the street Mouzinho da Silveira was planned and built. Aspiring to accelerated mobility, the knowledge of military engineering in topography was applied to the planning of infrastructures such as streets, bridges, railways and tunnels in order to reconfigure entrances and circuits between the main centres of activity (downtown and uptown). Meanwhile, overpopulation and disease required medical-based knowledge about epidemiology and public health to improve inhabited spaces. In juxtaposition, the city intersected these spheres, creating complex spatial models and new policies to control human activities. This environmental change was multifocal in European cities and solutions were devised in Lisbon, Paris and London. Considering its particular influence, it is intended to acknowledge the specific way this input was achieved and applied according to the specific conditions of Porto.
Keywords: Mouzinho da Silveira; Public Health; Public Works; Public Water System; Housing; Biopolitics